The role of loyalty programmes on retail fuel site profitability in Gauteng - Mtungwa, Muzi (University of the Witwatersrand, Johannesburg, 2021)
Loyalty programmes are one of a number of instruments used by businesses to retain existing customers, attract new customers and in the process retain them over a long term to sustain business profitability. They have been extensively investigated in the developed world with models developed to explain their role in customer retention. In the developing world, they are still being studied to understand if the models that have been developed in the developed world can be extended to the developing countries. Loyalty programmes were extended to the fuel retail industry in 2010 by First National Bank (FNB) and its oil partner, Engen Petroleum. The role of these programmes in the fuel retail industry and their correlation to profitability, whether positive or negative has received little attention from researchers. Here, the author reports on the correlation of these programmes to business profitability. The report shows that there is a positive correlation between these programmes and the profitability of an oil company, while at the same time the report supports the assertion by the non-loyalty programme oil companies that these programmes have a negative effect on their business. These non- loyalty programme oil companies which have a market share of less than 7 percent have been forced to exit the retail industry due to the introduction of these programmes by the major oil companies and their partners. The findings recommend that the role of these programmes in the fuel retail industry is further researched as the authourities do not allow for discounting of the retail price of petrol
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Loyalty programmes; Loyalty programs; Reward programme; UCTD; SDG-8: Decent work and economic growth